An atypical case of Hereditary Leiomyomatosis and Renal Cell Cancer (HLRCC)-associated renal cell carcinoma identified by next-generation sequencing - Daniel R. Matson, M.D., Ph.D; Molly A. Accola, Ph.D; William M. Rehrauer, Ph.D; Wei Huang, M.D (Elsevier, 2018)
Germline mutations in the fumarate hydratase (FH) gene classically lead to Hereditary Leiomyomatosis and Renal Cell Cancer (HLRCC) syndrome. Patients with HLRCC typically exhibit multiple cutaneous and uterine leiomyomas at a young age. They also display a 20-30% lifetime risk for renal carcinomas, which commonly present before 40 years of age, have a distinct papillary morphology, and an aggressive phenotype. However, the clinical presentation of HLRCC and the morphology of HLRCC-associated renal cell carcinomas (RCCs) can be variable and thereby evade diagnosis. Here, we present two cases of HLRCC-associated RCC to emphasize this point. The first case is typical of HLRCC, involving a 29-year-old man with multiple cutaneous leiomyomas and a renal tumor with characteristic papillary morphology. Next, we describe a 48-year-old man presenting with metastatic cancer of unknown primary origin and no skin findings. Interestingly, next-generation sequencing of his metastatic tumor identified two unique FH mutations. In both cases, FH mutations were confirmed as germline. These cases highlight the variable presentations of HLRCC-associated RCC and underscore the importance of screening tumors of unknown origin for FH mutations using next-generation sequencing. Keywords: Renal cell carcinoma, HLRCC, Fumarate hydratase, Next-generation sequencing